Sistem Pakar Diagnosa Iskemia Menerapkan Metode Fuzzy Sugeno - Siregar, Sari Mutiara (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
In general, many people cannot afford the services of specialist doctors in the field of diagnosing ischemic disease due to large consultation fees so they cannot get information related to the diagnosis of ischemic disease that is experienced. To solve the problems above, it is necessary to have a tool in the form of an expert system that has the same abilities as specialist doctors in the field of diagnosing ischemia disease, therefore this study designed an expert system for diagnosing ischemia disease using the fuzzy Sugeno method with the Visual Basic 2008 programming language. The results of this study can make it easier for the public in general to obtain information related to the diagnosis of ischemic disease that is experienced according to the ability of specialist doctors in the field of ischemia diagnosis